2013
DOI: 10.4269/ajtmh.13-0049
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Blood Stage Plasmodium falciparum Suppresses Malaria Super-Infection in a Malaria Holoendemic Population

Abstract: Abstract. Recent studies of Plasmodium berghei malaria in mice show that high blood-stage parasitemia levels inhibit the development of subsequent liver-stage infections. Whether a similar inhibitory effect on liver-stage Plasmodium falciparum by blood-stage infection occurs in humans is unknown. We have analyzed data from a treatment-time-toinfection cohort of children 10 years of age residing in a malaria holoendemic area of Kenya where people experience a new blood-stage infection approximately every 2 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This cohort has been described in detail in several publications [6][7][8][9]. Immediately after collection of blood samples, all participants were given a 6-dose regimen of artemether-lumefantrine to clear blood-stage infection without foreknowledge of whether the individual's blood smear was P. falciparum positive or negative.…”
Section: Study Participants and Designmentioning
confidence: 99%
“…This cohort has been described in detail in several publications [6][7][8][9]. Immediately after collection of blood samples, all participants were given a 6-dose regimen of artemether-lumefantrine to clear blood-stage infection without foreknowledge of whether the individual's blood smear was P. falciparum positive or negative.…”
Section: Study Participants and Designmentioning
confidence: 99%
“…The model assumes that for a given EIR, infective bites arrive randomly with exponentially distributed waiting times (13,34,35). Each bite infection then has a probability of reaching the blood stage, which is determined by the baseline probability of success (R b ) and the level of induced resistance at a given time [R(t)].…”
Section: ) (E) Parasite Liver Loads In Reinfected Ifnar1mentioning
confidence: 99%
“…To take these dynamics into consideration, we developed a stochastic model of malaria infection that takes into account more-complex factors such as multiple consecutive bites and gradual acquisition and loss of immunity. Our model is based on four assumptions: (i) infective bites arrive randomly at a given biting rate (13,34,35); (ii) only a proportion of bites result in infection (e.g., in a number of cases, mosquito injection of sporozoites is unsuccessful or sporozoites remain in the skin); (iii) a successful liver-stage infection (i.e., an infection that progresses to the blood stage) induces strong host resistance and thus inhibits the establishment of a subsequent liver-stage infection; and (iv) a liver-stage infection that is blocked by innate immunity and does not progress to a blood-stage infection nonetheless induces a small amount of resistance to subsequent infections.…”
Section: Induction Of Type I Ifn and Ifn-␥ By A First P Berghei Livementioning
confidence: 99%
See 1 more Smart Citation
“…The relative importance of co-inoculation versus superinfection is setting dependent and not yet fully understood. Previous studies found that parasite density in blood-stage can limit subsequent development of new sporozoites supporting the parasite population of first-inoculated genotype [47,48]. Hence, superinfection may be limited.…”
Section: Methodsmentioning
confidence: 98%